2016
DOI: 10.1007/s00436-016-5346-1
|View full text |Cite
|
Sign up to set email alerts
|

The p38 MAPK inhibitor, SB203580, inhibits cell invasion by Neospora caninum

Abstract: The Apicomplexan parasite Neospora caninum is an obligate intracellular parasitic protozoan. It can cause severe diseases in a number of animals throughout the world. Infection with N. caninum leads to abortions in pregnant animals and neuromuscular disorders of newborns which cause great economic losses to animal husbandry. However, the mechanism of cell invasion by N. caninum is still unclear. This paper aims to investigate the impact of SB203580, a p38 MAPK inhibitor, on host cell invasion by N. caninum. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…69 However, SB203580 is mostly used in vitro or in animal experiments due to low drug selectivity and a high rate of toxic side effects. [70][71][72] Other types of inhibitors, including pyridines, pyrimidines and indoles, also have the same problem. Pamapimod (PAM), a novel p38MAPK inhibitor firstly discovered in 2008, could improve the signs and symptoms of RA and other autoimmune diseases.…”
Section: P38mapk Pathway As Therapeutic Targets In Oa Treatmentmentioning
confidence: 99%
“…69 However, SB203580 is mostly used in vitro or in animal experiments due to low drug selectivity and a high rate of toxic side effects. [70][71][72] Other types of inhibitors, including pyridines, pyrimidines and indoles, also have the same problem. Pamapimod (PAM), a novel p38MAPK inhibitor firstly discovered in 2008, could improve the signs and symptoms of RA and other autoimmune diseases.…”
Section: P38mapk Pathway As Therapeutic Targets In Oa Treatmentmentioning
confidence: 99%
“…The previous research show that the p38 MAPK signaling pathway may play an important role in regulating the odontoblastic differentiation of hDPSCs (Gong et al, ; He et al, ; Yao et al, ), but the potential mechanism still remains controversial. Interestingly, a recent study has demonstrated that miR‐143 could regulate the expression of the p38 MAPK signaling pathway (Li et al, ). Moreover, another study shows that the p38 MAPK signaling pathway inhibitor SB203580 suppresses toxoplasma gondii MAPK1 autophosphorylation and blocks intracellular toxoplasma gondii replication by directly effecting tachyzoites (Jin, Gong, Li, Zhang, & Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study has demonstrated that miR-143 could regulate the expression of the p38 MAPK signaling pathway (Li et al, 2017). Moreover, another study shows that the p38 MAPK signaling pathway inhibitor SB203580 suppresses toxoplasma gondii MAPK1 autophosphorylation and blocks intracellular toxoplasma gondii replication by directly effecting tachyzoites (Jin, Gong, Li, Zhang, & Li, 2017). In the present research, SB203580, an inhibitor of the p38 MAPK signaling pathway, was used to verify whether miR-143-5p positively regulates the p38 MAPK signaling pathway by targeting MAPK14.…”
Section: Discussionmentioning
confidence: 99%
“…Serine protease inhibitors block invasion of host cells by Plasmodium falciparum ( Conseil et al, 1999 ) and Toxoplasma ( Alam, 2014 ). In Apicomplexan parasites, several kinases have been identified ( Brumlik et al, 2011 ; Wei et al, 2013 ; Brown et al, 2014 ; Jin et al, 2017 ). In addition, the existence of parasite receptor kinase protein homologs similar to mammalian host cells implies that N. caninum EGFR might participate in host immune evasion by the parasite, which needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%